Pengaruh berbagai formula pupuk bio-organo mineral terhadap N, P, K tersedia tanah dan pertumbuhan tanaman jagung - R. Agus Widodo; Didi Saidi; Djoko Mulyanto (Jurnal Ilmu Tanah dan Air, 2018)
The effect of bio-organo mineral fertilizers on availability of soil NPK andgrowth of corn plants (R. Agus Widodo, Didi Saidi, and Djoko Mulyanto): Thedemand of chemical fertilizers increase continuously, but the availability and high prices are obstacles to achieving optimal agricultural production. On the other hand, the dose of fertilizer that must be given per unit area continues to increase due to land degradation due to excessive use of chemicals without organic fertilizer. Organic giving is felt to be unable to meet the nutrient requirements needed by plants. Bio organo mineral fertilizer is an organic fertilizer enriched with agricultural mineral materials. This study aims to determine the effect of various formulas of bio-organo mineral fertilizer on the growth of corn plants. The study was conducted with experiments arranged in a randomized design complete with the treatment of 7 kinds of bio organo mineral fertilizers of various formulas and controls. Research parameters included plant height, stem diameter and number of leaves. The results showed that various bio organo mineral fertilizers had a significant effect on plant height and stem diameter, but were not significantly different from the number of leaves. The best fertilizer based on plant growth is bio-organomineral fertilizer with formula P4, which is a combination of 65% straw; 15% chicken manure; 20% agromineral material (Zeolite: Feldspar: Phosphate rock = 1: 1: 2)